ОЦЕНКА ЗНАЧИМОСТИ ХОЛТЕРОВСКОГО МОНИТОРИРОВАНИЯ ЭКГ В ДЕТСКОЙ ПРАКТИКЕ - Мусатова, Людмила Александровна; Краснова, Людмила Ивановна; Рушакова, Светлана Дмитриевна; Рушаков, Вадим Евгеньевич; Юсупова, Юлия Сулеймановна (FORCIPE, 2022)